Perspectives of Spanish-Speaking Caregivers on Pediatric Patient Portal Use - Tse, Gabriel; Squires, Stephanie; Hu, Katherine; Kelly, Michelle M.; Halpern-Felsher, Bonnie; Carlson, Jennifer (Applied Clinical Informatics, 2025)
Disparities exist in patient portal use among non-English-speaking caregivers of pediatric patients. This study aims to evaluate the reasons behind Spanish-speaking caregivers' use of patient portals and identify facilitators and barriers, focusing on those caring for children with chronic conditions.We conducted semi-structured interviews and surveys with Spanish-speaking caregivers of pediatric patients with chronic conditions at an academic pediatric health network in California. Data were transcribed, coded, and analyzed using inductive thematic analysis.Twenty caregivers participated. Participants primarily accessed patient portals via their smartphones, and most accessed the patient portal at least weekly. Three main themes emerged: perceived benefits (managing appointments, medications, and results), facilitators that improved use (support from healthcare professionals), and barriers that negatively affected use (differences in language, health literacy, and digital health literacy).Spanish-speaking caregivers find patient portals beneficial but face significant barriers related to language discordance and differences in health literacy and digital health literacy. This study highlights the need for health systems to provide language concordance within patient portals and consider innovative solutions that promote equitable use.
Keywords: patient portals; digital health; language equity